STUDI KASUS : KEPUTUSAN OPERATIF PADA KASUS PANGGUL SEMPIT DENGAN PRESENTASI KEPALA: STUDI KASUS SEKSIO SESARIA - Hitipeuw, Anthoneta J.; Achmad, Ismiyanti H. (Poltekkes Kemenkes Maluku, 2025)
In the world of obstetrics and gynecology, narrow pelvis or narrow pelvimetry often causes a mismatch between the size of the fetus and the birth canal called cephalopelvic disproportion (CPD). A narrow pelvis is one of the main causes of CPD, which is often an indication for cesarean section. In cases like this with a head presentation and narrow maternal pelvis, the risk of prolonged labor and complications increases significantly. Cesarean section is the main intervention of choice to save the life of the mother/baby so that it has an impact on reducing morbidity and mortality rates. However, if the implementation is not carried out on time or is repeated, it has significant physiological and psychosocial impacts. Various studies have shown that cesarean section intervention in cases of narrow pelvis significantly reduces the risk of obstetric complications in both the mother and the baby. Although cesarean section is effective in preventing morbidity and mortality, this procedure can also be at risk of causing postoperative complications and perinatal disorders if not carried out in a timely manner. This case study aims to describe the handling of cases of narrow pelvis with head presentation through cesarean section and the clinical impact on the mother and baby. Cesarean section in cases of narrow pelvis with cephalic presentation has been proven effective in preventing labor complications. Early diagnosis and appropriate action decisions are essential to ensure the safety of the mother and baby.